Privatization and Regulation of Transport Infrastructure : Guidelines for Policymakers and Regulators - Estache, Antonio (Washington, DC: World Bank, 2013)
The 1990s saw a dramatic increase in the liberalization of transport policies and a strengthening of the role played by private operators and investors in transport infrastructure. Most of these reforming countries are creating new regulatory agencies. This book aims is to contribute to the development of these regulatory skills. The book has two parts. Chapter 2 in the first part provides an overview of why economic regulation is important. It provides theoretical support to the sector-specific chapters that constitute the second part of the book. The second part covers four subsectors: airports, ports, railways, and roads. Each chapter follows exactly the same structure. The first section provides snapshot of the key economic characteristics of the sector and discusses their relevance from the viewpoint of a regulator. The second section summarizes the main privatization and regulation trends that have been observed in the sector. It gives an overview of main options offered by international experience and covers a few case studies that illustrate those options. The third section covers price regulation and highlights the price-related issues that characterize the sector. The fourth section does the same for quality regulation. The fifth section discusses the main performance indicators that the sector's regulators should be able to rely on to be effective in their jobs.